Assay of Escherichia coli enterotoxins by in vivo perfusion in the rat jejunum. - Klipstein, F A (1976)
Assay of Escherichia coli enterotoxins by in vitro perfusion in rats was evaluated by examining the effects of variously prepared fractions of heat-labile (LT) and heat-stable (ST) toxins on water transport in this system. The assay was found to respond equally well, in a dose-related manner, to both LT and ST; it was sufficiently sensitive to detect the toxigenic effect of concentrations as small as 1 ng/ml. With the assay, it was found that LT is produced in cultures grown under aerobic, but not anaerobic, conditions; in contrast, ST is elaborated in stationary aerobic and anaerobic broth cultures but not in those grown under agitated aerobic conditions. Both toxins can be precipitated by either ammonium sulfate or acetone. The two toxin forms were completely separated from each other by sequential ultrafiltration. LT alone (thermolabile after exposure to 100 degrees C for 30 min) was retained by a PM-30 membrane, and ST alone was present in UM-2 retentates; ST was retained more effectively by a UM-05 membrane, with a 1,000-fold increase in activity over that of the UM-2 retentate. Washed ultrafiltration retentates containing either LT or ST derived from the proper culture conditions all induced water secretion at concentrations of 100 ng or less per ml. These results indicate that in vivo perfusion in rats is a sensitive, duplicable assay for both the LT and ST forms of E. coli enterotoxin.